The contribution of provitamin A biofortified cassava to vitamin A intake in Nigerian pre-schoolchildren. Issue 9 (14th November 2021) - Afolami, Ibukun; Samuel, Folake; Borgonjen-van den Berg, Karin; Mwangi, Martin N.; Kalejaiye, Olatundun; Sanusi, Rasaki A.; Putri, Linda Ayu Rizka; Brivio, Francesca; Brouwer, Inge D.; Melse-Boonstra, Alida
Abstract: Biofortified yellow cassava has been developed to alleviate vitamin A deficiency. We examined the potential contribution of yellow cassava to total retinol activity equivalent (RAE) intake if replacing white by yellow cassava among pre-school Nigerian children. Dietary intake was assessed as part of a randomised controlled trial. Pre-schoolchildren ( n 176) were randomly assigned to receive either white cassava (WC) or yellow cassava (YC) for 17 weeks. Dietary intake assessments were conducted during the intervention and 1 month after, when children had resumed their habitual diet. Differences in RAE intake between groups and time points were compared using a linear mixed model regression analysis. During intervention, median RAE intake was 536 µg/d in the YC group and 301 µg/d in the WC group ( P < 0·0001). YC contributed approximately 40 % to total RAE intake. Of the children, 9 % in the YC group and 29 % in the WC group had RAE intake below the Estimated Average Requirement. After intervention, median RAE intake was 300 µg/d and did not differ between intervention groups ( P = 0·5). The interaction effect of group and time showed a 37 % decrease in RAE intake in the YC group after the intervention (Exp( β ) = 0·63; 95 % CI 0·56, 0·72). If WC was replaced by YC after intervention, the potential contribution of YC to total RAE intake was estimated to be approximately 32 %. YC increased total RAE intake and showed a substantially lower inadequacy of intake. It is therefore recommended as a good source of provitamin A in cassava-consuming regions.